Literasi Akuntansi Bisnis untuk Pemberdayaan Para Santri - Zenabia, Tsarina; Ahmad, Syauqi; Zaldy, Suhatman (Abdimisi, 2025)
In the era of globalization and digitalization, accounting literacy is crucial for Micro, Small, and Medium Enterprises (MSMEs) to maintain business sustainability. However, many MSME actors, especially those within the Al Kamilah Islamic Boarding School Foundation, have limited understanding of financial recording and accounting reporting. The main issue lies in the limited knowledge of bookkeeping and reporting, as well as unstructured financial management that has yet to adapt to the use of digital accounting technology. This condition hinders strategic decision-making, profit monitoring, capital management, and access to funding. This community service activity aims to improve the students’ understanding of basic accounting, recording skills, financial management, and the preparation of simple financial reports by utilizing digital accounting technology. The method used is a participatory approach involving active engagement of the students. As a result, their skills in financial recording and the use of digital applications have improved, and financial reports have become more structured and transparent. This program has enhanced accounting literacy and digital-based financial management for business. A continuous program of assistance and digital marketing training is needed to optimally support business development. Keywords: Islamic Boarding School; Accounting Literacy; Financial Management